Further contributions to the flora of lichens and lichenicolous fungi of the Azores. - Berger, Franz (2002)
Several lichens are reported new to the flora of the Azores. Mycoporum sparsellum, and the lichenicolous coelomycete Laeviomyces fallaciosus are reported for the first time in Europe. Arthothelium crozalsianum, Bacidia friesiana, Belonia incarnata, Julella sericea, Micarea assimilata, Mycomicrothelia confusa and Roselliniopsis ventosa are recorded for the first time in Laurimacaronesia. New for the Azores are Acarospora umbilicata, Buellia aethalea, B. subdisciformis, Byssoloma marginatum, Canoparmelia texana, Catillaria atomarioides, Chaenotheca furfuracea, Chromatochlamys muscorum, Cladonia cyathomorpha, C. pocillum, C. rangiformis var. gracillima, Cliostomom griffithii, Endocarpon pusillum, Hypotrachyna taylorensis, Opegrapha ochrocheila, O. vermicellifera, O. vulgata, Parmotrema mellissii, Peltula euploca, Pertusaria hymenea, Phaeophyscia hispidula, Porina aenea, P. borreri, Pyrenula acutispora, Ramalina lacera, R. subpusilla, Rinodina anomala, R. intermedia, Scoliciosporum umbrinum, Strigula taylorii, Toninia mesoidea, Xanthoria candelaria and X. fallax. Fourteen additional lichenicolous fungi double the list of species from the Azores.